Method for improving crystallization quality of ammonium sulfate solution
By introducing fluorine elements into the ammonia desulfurization process, the median stability zone and super solubility curve of the ammonium sulfate solution are regulated, and the problem of poor crystallization quality of ammonium sulfate at high temperatures in summer is solved, and the stability and quality improvement of ammonium sulfate crystallization is achieved.
Patent Information
- Application Number
- CN202411822015.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
Under high temperature conditions in summer, in the ammonia desulfurization process, due to the high inlet temperature of the flue gas in the concentration section of the desulfurization tower, the by-product ammonium sulfate crystal grains are small and difficult to separate.
By introducing fluorine elements into the ammonium sulfate solution, the width of the mesolidity zone and the position of the super-solubility curve of the ammonium sulfate solution are controlled so that the ammonium sulfate solution is in the mesolidity zone even at high concentrations, avoiding explosive nucleation.
It effectively improves the crystal quality of ammonium sulfate, avoids the problems of poor crystallization and difficulty in discharge caused by high temperatures in summer, and ensures the stability and quality of ammonium sulfate products.
Smart Images

Figure CN119607605A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial crystallization optimization, and in particular relates to a method for improving the crystallization quality of an ammonium sulfate solution. Background Art
[0002] Although the proportion has been declining year by year, thermal power generation still occupies a very important position in China's power structure. The main fuels for thermal power generation include fossil energy such as coal, oil and natural gas. Since China has abundant coal resources, coal is the main fuel for thermal power generation in my country. However, since coal contains sulfur, it will be oxidized into sulfur dioxide (SO2) when burned. If it is allowed to be discharged into the atmosphere, it will form pollutants such as acid rain and aerosols, which will seriously endanger human health and the sustainable development of the environment. In order to make the SO2 in the flue gas meet the standards, thermal power plants often need to take certain desulfurization measures. There are many types of flue gas desulfurization technologies, and ammonia desulfurization has obvious advantages over other processes: 1) High desulfurization efficiency, with a SO2 removal rate of more than 90% in flue gas; 2) Ammonia reacts quickly with SO2, and the desulfurization process can be completed in a relatively short time; 3) Strong adaptability, suitable for the treatment of coal combustion flue gas with different sulfur contents; 4) The generated ammonium sulfate can be recycled as fertilizer after crystallization, drying and separation.
[0003] The general process flow of flue gas ammonia desulfurization is as follows: Figure 1 As shown, based on the reaction of NH3 and SO2 in aqueous solution, an aqueous solution of ammonium sulfite or ammonium bisulfite is obtained as an intermediate product, and then compressed air is blown into the oxidation section for oxidation reaction to directly oxidize the ammonium sulfite into ammonium sulfate solution; in the concentration section, high-temperature flue gas enters from the middle and lower part, and exchanges heat with the saturated ammonium sulfate solution separated and returned from the circulation tank to obtain ammonium sulfate slurry with a certain solid content. The slurry is centrifuged, dried, and other processes to obtain the ammonium sulfate product. The main reaction mechanism is as follows:
[0004] <![CDATA[SO2+NH3+H2O=NH4HSO3]]> (1) <![CDATA[SO2+2NH3+H2O=(NH4)2SO3]]> (2) <![CDATA[SO2+(NH4)2SO3+H2O=2NH4HSO3]]> (3) <![CDATA[NH3+NH4HSO3=(NH4)2SO3]]> (4) <![CDATA[2(NH4)2SO3+O2=2(NH4)2SO4]]> (5)
[0005] At present, the ammonia desulfurization process often has the problem of poor crystallization quality of ammonium sulfate products. Part of the reason is that the sintering flue gas contains a variety of impurities, which leads to periodic abnormal crystallization of the system. This problem can be basically solved after the flue gas dust removal meets the standards; in some cases, the flue gas temperature in contact with the ammonium sulfate mother liquor is too high, causing the water in the ammonium sulfate solution to evaporate rapidly during heat exchange with the flue gas, and the solution concentration increases too quickly, exceeding the super solubility curve and then falling into the unstable zone above the metastable zone, causing the solution to undergo explosive nucleation. The ammonium sulfate crystal size is small, and the solid and liquid phases are difficult to separate. This situation often occurs in the summer when the temperature is high.
[0006] Solubility refers to the maximum concentration of a substance (solute) when it reaches thermodynamic equilibrium in another liquid or solid substance (solvent) at a specific temperature and pressure. Figure 2 As shown, the solubility curve is a curve drawn by the solubility of the same substance at different temperatures; the limiting concentration that indicates that the solution is supersaturated and wants to spontaneously produce crystal nuclei is called supersolubility; the area between the solubility curve and the supersolubility curve is called the metastable zone, which is the best operating area for the crystallization process. The solution will not spontaneously nucleate in the metastable zone. The wider the metastable zone, the more stable the supersaturated solution. Therefore, the key to avoiding the explosive nucleation of the solution and improving the quality of ammonium sulfate crystallization lies in how to widen the width of the metastable zone and ensure that the solution crystallizes in the metastable zone; especially for the high temperature weather in summer, when the flue gas carries too much heat, it is necessary not only to increase the width of the metastable zone, but also to pay special attention to the position of the supersolubility curve. The higher the supersolubility curve is, the concentration of the ammonium sulfate solution after obtaining higher energy through heat exchange with the flue gas can also fall in the metastable zone below the supersolubility curve, which is more suitable for high temperature conditions in summer.
[0007] Fluoride ion (F - ) Because of its strong electronegativity, each F in the solution - The surrounding area can attract a number of ammonium ions (NH4 + ), avoiding the NH4 + With sulfite (SO3 2- ), sulfate (SO4 2- ) combine too quickly and tightly, so that the ammonium sulfate solution in the system can remain stable even at a higher concentration, and spontaneous nucleation does not occur, that is, the solution is in the metastable zone at high concentrations.
[0008] Chinese patent CN102826572A discloses a flue gas ammonia desulfurization byproduct refining process, which solves the problem of dust removal affecting product quality in the existing refining process. The ammonium sulfate product is obtained mainly through three process steps: solid-liquid separation, membrane oxidation, and concentration and cooling. However, the patent does not regulate the metastable zone and super solubility curve, nor does it add the key component fluorine, which is mainly used for dust removal.
[0009] Chinese patent CN106345257A discloses a device and method for improving the quality of ammonium sulfate produced as a byproduct of ammonia desulfurization, the device including a desulfurization tower and an ammonium sulfate crystallization system. The patent mainly achieves the purpose of improving the quality of ammonium sulfate produced as a byproduct of ammonia desulfurization by optimizing the system flow of the device and controlling the pH value, temperature and oxidation rate of the slurry. However, the patent does not regulate the metastable zone and super solubility curve, nor does it add the key component fluorine.
[0010] Chinese patent CN115417430A discloses a method and application of mixing ammonium chloride and ammonium nitrate to regulate the metastable zone of ammonium sulfate, and uses different ratios of ammonium chloride and ammonium nitrate to regulate the metastable zone of ammonium sulfate crystallization, thereby obtaining large-particle high-quality ammonium sulfate crystals. However, the patent does not add fluorine, nor does it explain the influence on the position of the super solubility curve, and has not been applied to industrial devices.
[0011] The document "Study on Crystallization of Ammonium Sulfate under the Action of Ammonium Nitrate" (Master's thesis of Kunming University of Science and Technology, 2022, Dai Meng) examined the effect of ammonium nitrate on the crystallization process of ammonium sulfate, and pointed out that as the amount of ammonium nitrate added increased, the solubility of ammonium sulfate decreased, and the metastable zone of ammonium sulfate crystallization became wider. However, this document widened the width of the metastable zone by shifting the solubility curve downward, and failed to change the position of the super solubility curve of the ammonium sulfate solution. Therefore, it was unable to cope with the situation of excessively high inlet flue gas temperature of the device during hot summer weather, and could not effectively avoid the explosive nucleation phenomenon of the ammonium sulfate solution. Summary of the invention
[0012] In order to solve the problem that in the traditional ammonia desulfurization process under high temperature conditions in summer, the by-product ammonium sulfate crystals are small and difficult to separate due to the high inlet temperature of the flue gas in the concentration section of the desulfurization tower, the present invention provides a method for improving the crystal quality of ammonium sulfate solution.
[0013] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0014] The present invention provides a method for improving the crystallization quality of ammonium sulfate solution, comprising the following steps:
[0015] Step S1: determination of solubility of ammonium sulfate solution;
[0016] A solubility determination test device is set up, deionized water is heated to an expected temperature T and kept constant; fluoride is weighed and added to ammonium sulfate, and ammonium sulfate samples with different fluorine contents are obtained after being fully mixed; the ammonium sulfate sample is weighed and added to the deionized water heated to the expected temperature T, and a constant rate of magnetic stirring is started, and the ammonium sulfate sample is added in small amounts multiple times until a very small amount of the ammonium sulfate sample cannot be dissolved within the specified time, and the total mass of the added ammonium sulfate sample is recorded, the solubility of the ammonium sulfate sample at the temperature T is calculated, and the corresponding solubility curve is drawn;
[0017] Step S2: Determination of the width of the metastable zone of the ammonium sulfate solution;
[0018] Weigh a certain amount of fluoride and add it to a certain amount of ammonium sulfate, mix them thoroughly and evenly to obtain ammonium sulfate samples with different fluorine contents; use a solubility test device to mix deionized water and the ammonium sulfate sample, and then use a water bath and a peristaltic pump to circulate and heat them, while starting a magnetic stirring at a constant rate until the ammonium sulfate sample is completely dissolved; build a metastable zone test device, quickly pour the obtained ammonium sulfate solution into a crystallization tube (7) in the metastable zone test device, and achieve natural cooling through the circulation of deionized water. The ammonium sulfate solution slowly cools down until the first crystal is precipitated in the crystallization tube (7), and the temperature T at this time is recorded. nuc ; Determine the temperature T of each ammonium sulfate sample with the same fluorine content and different concentrations nuc , draw the super solubility curve of each sample and calculate the width of its metastable zone respectively;
[0019] Step S3: Determine the optimal amount of fluorine added based on the solubility of the ammonium sulfate sample calculated in step S1 and the metastable zone width of the ammonium sulfate solution calculated in step S2, and introduce fluorine into the flue gas ammonia desulfurization system so that the ammonium sulfate solution in the system can be within the metastable zone when the concentration is high.
[0020] Further, the solubility determination test device comprises:
[0021] Jacketed crystallizer;
[0022] A magnetic stirrer installed at the lower end of the jacketed crystallizer;
[0023] A magnetic stirring bar placed at the bottom of the jacketed crystallizer;
[0024] a water bath connected to the jacketed crystallizer via a first peristaltic pump;
[0025] Two first digital thermometers, one of which is mounted on the jacketed crystallizer and a measuring end of the first digital thermometer is inserted into the jacketed crystallizer, and the other first digital thermometer is mounted on the water bath and a measuring end of the first digital thermometer is inserted into the water bath;
[0026] Accurately measure a certain amount of deionized water and pour it into a water bath, use the water bath to heat the deionized water to the expected temperature T and keep it constant, then use the first peristaltic pump to transport the deionized water heated to the expected temperature T to the jacketed crystallizer, and at the same time transport the deionized water in the jacketed crystallizer back to the water bath for circulation heating to keep the deionized water temperature constant at the expected temperature T; during the heating process, the deionized temperature is checked in real time by the first digital thermometer.
[0027] Furthermore, the metastable zone determination test device comprises:
[0028] Iron frame platform;
[0029] A crystallization tube fixed on an iron frame, wherein the crystallization tube is a three-layer crystallization tube structure, wherein the innermost layer is used for standing and crystallizing the ammonium sulfate sample solution, the middle layer is used for running water to maintain the temperature of the ammonium sulfate sample solution, and the outermost layer is an air layer for further heat preservation;
[0030] A beaker connected to the middle layer of the crystallization tube through a second peristaltic pump, the lower end of the crystallization tube is inserted into the beaker, and the water level in the beaker is above the lower water inlet of the crystallization tube;
[0031] A second digital thermometer is mounted on the crystallization tube and the measuring end is inserted into the crystallization tube.
[0032] Furthermore, in step S1, the expected temperature is 30°C to 90°C.
[0033] Furthermore, in step S1, in the ammonium sulfate samples with different fluorine contents, the proportion of fluoride ions is 0.1% to 20%.
[0034] Furthermore, in step S1, the fluoride is selected from one of ammonium fluoride, sodium fluoride, calcium fluoride and aluminum fluoride.
[0035] Furthermore, in step S1, the fluoride is ammonium fluoride, and the amount of ammonium fluoride added to the ammonium sulfate sample m(NH4F) is calculated as follows:
[0036] because Therefore, the mass of ammonium fluoride added
[0037] in, is the mass percentage (%) of fluorine element in the ammonium sulfate sample, n is the amount of fluorine element and ammonium fluoride substance added, m(water) is the mass of deionized water, M(F) is the relative atomic mass of fluorine, and M(NH4F) is the molecular weight of ammonium fluoride.
[0038] Further, in step S1, the calculation formula of the solubility S of the ammonium sulfate sample is as follows:
[0039]
[0040] Among them, m 总 is the total mass of the ammonium sulfate sample, m 水 is the mass of the solvent, i.e., deionized water.
[0041] Furthermore, the constant speed range is 150r / min to 1500r / min.
[0042] Furthermore, in step S2, the calculation method of the metastable zone width is as follows:
[0043] The width of the metastable zone refers to the distance between the supersolubility curve and the solubility curve of the system. The vertical distance represents the maximum supersaturation Δc. max :
[0044] Δc max =c0-c2
[0045] Where c0 is the saturated concentration of ammonium sulfate solution at a certain temperature, and c2 is the concentration at which crystal nuclei appear at that temperature;
[0046] Its horizontal distance represents the maximum undercooling ΔT max , which is the difference between the saturation temperature and the nucleation temperature:
[0047] ΔT max =T0-T nuc
[0048] Among them, T0 is the saturation temperature of the solution at a certain concentration, T nuc is the temperature at which the crystal nucleus appears at this concentration;
[0049] Maximum supersaturation Δc max and maximum subcooling ΔT max The relationship between them is:
[0050]
[0051] Where dC* / dT is the slope of the solubility curve.
[0052] The beneficial effects of the present invention are:
[0053] The present invention provides a method for improving the crystallization quality of ammonium sulfate solution. Firstly, the influence of the amount of fluorine element addition on the metastable zone of the ammonium sulfate solution is determined in a laboratory through solubility determination, cooling crystallization, analysis and calculation, etc., and the most suitable addition ratio is found; then, the fluorine element is introduced into the system, so that the ammonium sulfate solution in the system can remain stable and not spontaneously nucleate even at a higher concentration, that is, it is also in the metastable zone at a high concentration, thereby avoiding the condition that the ammonium sulfate solution has explosive nucleation due to the concentration exceeding the super solubility curve falling in the unstable zone due to the excessively high smoke temperature in summer, thereby causing poor crystallization and difficult discharge.
[0054] Compared with the prior art, the present invention has the following advantages:
[0055] (1) The present invention adds fluorine to shift the super solubility curve of the ammonium sulfate solution upward, broaden the upper limit of the metastable zone of the ammonium sulfate solution, and increase the maximum heat exchange capacity that a unit saturated ammonium sulfate solution can withstand.
[0056] (2) The present invention regulates the range of the metastable zone of the ammonium sulfate solution by adding fluorine, increases the width of the metastable zone, and reduces the probability of explosive nucleation of the ammonium sulfate solution due to falling into the unstable zone during crystallization, thereby making it easier to obtain large-particle ammonium sulfate crystals with better quality.
[0057] (3) The present invention introduces fluorine into the industrial desulfurization device system to avoid the situation where the unit heat exchange of the saturated ammonium sulfate solution exceeds the upper limit due to the excessively high smoke temperature in summer, which in turn causes the solution concentration to exceed the super solubility curve and fall into the unstable zone, resulting in explosive nucleation and poor crystallization of ammonium sulfate and difficulty in discharging.
[0058] (4) The method of improving the crystallization quality of ammonium sulfate solution of the present invention solves the problem of poor crystallization of ammonium sulfate in the existing ammonia desulfurization process. The present invention does not require changes to the existing device process, is simple in method, low in cost, and is suitable for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a schematic diagram of the process flow of the desulfurization section of the device.
[0060] Figure 2 Schematic diagram of the metastable zone.
[0061] Figure 3 Schematic diagram of the solubility determination test apparatus.
[0062] Figure 4 Schematic diagram of the experimental device for metastable zone determination.
[0063] Figure 5 Schematic diagram for calculating the width of the metastable zone.
[0064] Figure 6 This is the improved process flow chart of the desulfurization section.
[0065] Figure 7 It is a comparison chart of metastable zone width of the example solutions.
[0066] Figure 8 This is a comparison chart of the metastable zone width of the comparative solutions.
[0067] Fig. 9 This is a comparison chart of the metastable zone width of the solutions of Comparative Example 2 and Example 1.
[0068] Fig.10 It is a crystal form of ammonium sulfate with poor crystal quality.
[0069] Fig.11 It is the crystal form of ammonium sulfate after adding an appropriate amount of fluorine.
[0070] The reference numerals in the figure are as follows: 1-jacketed crystallizer, 2-first digital thermometer, 3-magnetic stirrer, 4-magnetic stirrer, 5-first peristaltic pump, 6-water bath, 7-crystallization tube, 8-beaker, 9-iron stand, 10-second digital thermometer, 11-second peristaltic pump. DETAILED DESCRIPTION
[0071] The present invention provides a method for improving the crystallization quality of ammonium sulfate solution, which mainly includes the following parts:
[0072] The first part is the laboratory test of the effect of fluorine addition on the solubility of ammonium sulfate solution. Figure 3 As shown, it is specifically implemented through the following technical solutions:
[0073] (1) A solubility determination test device is constructed, which mainly includes: a jacketed crystallizer 1, two first digital thermometers 2, a magnetic stirrer 3, a magnetic stirrer 4, a first peristaltic pump 5 and a water bath 6. The magnetic stirrer 3 is installed at the lower end of the jacketed crystallizer 1, and the magnetic stirrer 4 is placed at the bottom of the jacketed crystallizer 1. One of the first digital thermometers 2 is installed on the jacketed crystallizer 1 and the measuring end of the first digital thermometer 2 is inserted into the jacketed crystallizer 1. The first peristaltic pump 5 is connected to the jacketed crystallizer 1 through a pipeline, and the water bath 6 is connected to the first peristaltic pump 5 through a pipeline. A first digital thermometer 2 is also installed on the water bath 6, and the measuring end of the first digital thermometer 2 is inserted into the water bath 6.
[0074] (2) Use a measuring cylinder to accurately measure a certain amount of deionized water and pour it into the water bath 6, use the water bath 6 to heat the deionized water to the expected temperature T and keep it constant, then use the first peristaltic pump 5 to transport the deionized water heated to the expected temperature T to the jacketed crystallizer 1, and at the same time, transport the deionized water in the jacketed crystallizer 1 back to the water bath 6 for circulation heating to keep the deionized water temperature constant at the expected temperature T; during the heating process, the deionized water temperature is checked in real time by the first digital thermometer 2.
[0075] The deionized water heated to the expected temperature T is the solvent of the prepared ammonium sulfate solution.
[0076] Among them, the heating method of deionized water is preferably heating in a water bath 6. The deionized water heated by the water bath 6 is then transported to the jacketed crystallizer 1 using the first peristaltic pump 5. At the same time, the deionized water in the jacketed crystallizer 1 is transported back to the water bath 6 for circulation heating to keep the system in continuous circulation.
[0077] The expected temperature T is preferably 30°C to 90°C.
[0078] (3) Calculate the amount of fluoride required for each ammonium sulfate sample with different fluoride ion proportions (0.1% to 20%), accurately weigh a certain amount of fluoride using an analytical balance (precision: ±0.0001 g) and add it to the weighed ammonium sulfate, mix thoroughly, and obtain ammonium sulfate samples with different fluoride contents.
[0079] The fluoride ion ratio refers to the mass percentage of fluoride ions in the ammonium sulfate sample.
[0080] Among them, fluorides include but are not limited to: ammonium fluoride, sodium fluoride, calcium fluoride, aluminum fluoride and the like.
[0081] The weighed ammonium sulfate refers to the quantitative amount of ammonium sulfate calculated according to the mass percentage of fluoride ions in the ammonium sulfate sample, on the premise that the method of introducing fluoride ions is determined.
[0082] Herein, fully mixing and uniformly mixing means: fully stirring the weighed fluoride and ammonium sulfate by glass rod, ball milling, mixing, ultrasound and the like, but is not limited thereto.
[0083] The mass m(NH4F) of ammonium fluoride added to the ammonium sulfate sample is calculated by the following method:
[0084] because Therefore, the mass of ammonium fluoride added is in, is the mass percentage (%) of fluorine element in the ammonium sulfate sample, n is the amount of fluorine element and ammonium fluoride substance added, m(water) is the mass of deionized water (100 g), M(F) is the relative atomic mass of fluorine (19), and M(NH4F) is the molecular weight of ammonium fluoride (37.04).
[0085] (4) Weigh a certain amount of the ammonium sulfate sample mixed in step (3) using an analytical balance (precision of ±0.0001 g) and add it to the jacketed crystallizer 1 in step (2), turn on the magnetic stirrer 3 at a constant speed and stir it using the magnetic stirrer 4, and add a certain amount of the ammonium sulfate sample in step (3) in small amounts and multiple times until a very small amount of the ammonium sulfate sample (the amount of the ammonium sulfate sample does not exceed 0.01 g, by naked eye observation) cannot be dissolved within a specified time (generally 10 min-30 min), and record the total mass m of the added ammonium sulfate sample. 总 , the solubility S of the ammonium sulfate sample at the temperature T is calculated by the following formula:
[0086]
[0087] In the formula, m 水 It refers to the quality of the solvent, i.e. deionized water.
[0088] The mixed ammonium sulfate sample refers to ammonium sulfate that is fully and evenly mixed with fluorides having different fluoride ion proportions.
[0089] The constant speed range is preferably 150 r / min to 1500 r / min, but is not limited thereto.
[0090] Among them, adding small amounts multiple times means: adjusting the amount of ammonium sulfate sample added each time according to the dissolution rate of the ammonium sulfate sample already added, to ensure that the solution can be fully saturated and there is not too much excess ammonium sulfate sample.
[0091] (5) Using the above method, the solubility of ammonium sulfate samples with different fluorine contents at different temperatures was determined.
[0092] (6) The obtained solubility data are plotted as a solubility curve to analyze the effect of fluorine content on the solubility of ammonium sulfate solution.
[0093] The second part is the laboratory test of the effect of fluorine addition on the width of the metastable zone of ammonium sulfate solution. Figure 4 As shown, it is specifically implemented through the following technical solutions:
[0094] 1) A metastable zone determination test device is constructed, which mainly includes: a crystallization tube 7, a beaker 8, an iron stand 9, a second digital thermometer 10 and a second peristaltic pump 11. The crystallization tube 7 is fixed on the iron stand 9, the lower end of the crystallization tube 7 is inserted into the beaker 8, the second digital thermometer 10 is installed on the crystallization tube 7 and the measuring end of the second digital thermometer 10 is inserted into the crystallization tube 7, one end of the second peristaltic pump 11 is connected to the middle layer of the crystallization tube 7 through a pipeline, and the other end of the second peristaltic pump 11 is connected to the beaker 8 through a pipeline.
[0095] The crystallization tube 7 is a three-layer crystallization tube structure, the innermost layer is used to place the crystallized ammonium sulfate sample solution, the middle layer is used to carry water to maintain the solution temperature, and the outermost layer is an air layer for heat preservation again.
[0096] 2) According to step (3) in the first part, ammonium sulfate samples with different fluorine contents are prepared for use; a certain amount of deionized water is accurately measured using a measuring cylinder and poured into the jacketed crystallizer 1, and a certain amount of ammonium sulfate samples with different fluorine contents are weighed using an analytical balance (precision is ±0.0001g) and added to the jacketed crystallizer 1, and a water bath 6 and a first peristaltic pump 5 are used for cyclic heating according to step (2) in the first part, and a magnetic stirrer 3 is turned on at a constant speed and stirred by a magnetic stirrer 4 until the ammonium sulfate sample is completely dissolved (no solid particles are visible to the naked eye, and the reading does not change when tested using a helium-neon laser transmitter).
[0097] The added deionized water is the solvent of the ammonium sulfate solution.
[0098] The constant speed range is preferably 150 r / min to 1500 r / min, but is not limited thereto.
[0099] 3) The ammonium sulfate solution obtained in step 2) is quickly poured into the crystallization tube 7, and the lower end of the crystallization tube 7 is inserted into a beaker 8 filled with deionized water. The temperature of the deionized water in the beaker 8 should be the same as the temperature of the deionized water in the water bath 6; the deionized water in the beaker 8 is transported to the middle layer of the crystallization tube 7 by a second peristaltic pump 11, and the deionized water in the middle layer of the crystallization tube 7 is transported back to the beaker 8. The deionized water circulation is used to achieve natural cooling, and the ammonium sulfate solution is slowly cooled until the first crystal is precipitated in the crystallization tube 7 (the first ammonium sulfate crystal can be seen by the naked eye, or the reading changes significantly when tested using a helium-neon laser transmitter), and the temperature T at this time is quickly recorded. nuc .
[0100] 4) Determine the temperature T of each sample with the same fluorine content and different concentrations of ammonium sulfate nuc , draw the super solubility curve and calculate the metastable zone width ΔT max .
[0101] The width of the metastable zone is calculated by the following method:
[0102] The width of the metastable zone refers to the distance between the supersolubility curve and the solubility curve of the system, such as Figure 5 As shown, the vertical distance represents the maximum supersaturation Δc max :
[0103] Δc max =c0-c2
[0104] Among them, c0 is the saturated concentration of ammonium sulfate solution at a certain temperature, and c2 is the concentration when crystal nuclei appear at this temperature.
[0105] Its horizontal distance represents the maximum undercooling ΔT max , which is the difference between the saturation temperature and the nucleation temperature:
[0106] ΔT max =T0-T nuc
[0107] Among them, T0 is the saturation temperature of the solution at a certain concentration, T nuc is the temperature at which crystal nuclei appear at this concentration.
[0108] Maximum supersaturation Δc max and maximum subcooling ΔT max The relationship between them is:
[0109]
[0110] Where dC* / dT is the slope of the solubility curve.
[0111] The third part, industrial application part, such as Figure 6 As shown, it is specifically implemented through the following technical solutions:
[0112] (1) Replace the type of coal with a higher fluorine content.
[0113] (2) If it is not possible to accurately select coals with different fluorine contents, it is necessary to make subtle improvements and optimizations to the process flow, such as Figure 6 As shown, a branch line is opened in the circulation tank of the desulfurization section, and a fluoride solution of a certain concentration is added to the circulation tank by a pump. The fluoride solution then follows the ammonium sulfate solution returning from the circulation tank to the concentration section of the desulfurization tower to circulate to the entire system, thereby adjusting the fluorine content in the ammonium sulfate solution in the system to achieve the purpose of increasing the metastable zone of the solution in the system and moving up the dissolution super solubility curve.
[0114] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0115] Example 1
[0116] The method for determining the solubility of ammonium sulfate solution and the width of the metastable zone in the laboratory test section of this embodiment is specifically implemented as follows:
[0117] Use a measuring cylinder to accurately measure 100 mL of deionized water and pour it into the water bath 6. Use the water bath 6 to heat the deionized water to the expected temperature T = 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C and keep it constant. Then use the first peristaltic pump 5 to transport the deionized water heated to the expected temperature T to the jacketed crystallizer 1, and at the same time transport the deionized water in the jacketed crystallizer 1 back to the water bath 6 for circulation heating.
[0118] Weigh 100g of ammonium sulfate. The fluorine element is introduced by ammonium fluoride. The amount of ammonium fluoride required to be added is 10.79g based on the mass percentage of fluoride ions in the ammonium sulfate sample being 5%. Put the weighed ammonium sulfate and ammonium fluoride into the same beaker, first stir them thoroughly with a glass rod and then mix them under ultrasonic conditions for 10 minutes to ensure that they are fully mixed.
[0119] Weigh 50g of the mixed ammonium sulfate sample using an analytical balance (precision ±0.0001g) and add it to the jacketed crystallizer 1 after the temperature stabilizes. Turn on the magnetic stirrer 3 and stir it with the magnetic stirrer 4 at a speed of 800r / min. Add the ammonium sulfate sample in small amounts and multiple times until a very small amount of the ammonium sulfate sample cannot be dissolved within 10 minutes. Record the total mass m of the ammonium sulfate sample added at each temperature T 总 , calculate the solubility S of the ammonium sulfate sample at each temperature T. The specific data are shown in the following table, and the solubility curve determination under this fluorine content is completed.
[0120] Table 1 Solubility curve measurement data of Example 1
[0121] Serial number Temperature T(℃) <![CDATA[Total mass m 总 (g)]]> Solubility S (g / 100g water) 1 30 79.1 0.791 2 40 80.5 0.805 3 50 83.6 0.836 4 60 86.2 0.862 5 70 90.6 0.906 6 80 96.4 0.964 7 90 106.7 1.067
[0122] Use a measuring cylinder to measure 100 mL of deionized water and pour it into the jacketed crystallizer 1. At the same time, use an analytical balance (precision is ±0.0001g) to weigh 100g, 95g, 90g, 85g, and 80g of the prepared ammonium sulfate sample with a fluorine content of 5%, and add them to the jacketed crystallizer 1 respectively. According to step (2) in the first part, use a water bath 6 and a first peristaltic pump 5 for cyclic heating. At the same time, turn on a magnetic stirrer 3 at a constant speed (speed of 800r / min) and stir with a magnetic stirrer 4 until the ammonium sulfate sample in the jacketed crystallizer 1 is completely dissolved; quickly pour the ammonium sulfate solution in the jacketed crystallizer 1 into the crystallization tube 7, use a second peristaltic pump 11 to transport the deionized water in the beaker 8 to the middle layer of the crystallization tube 7, and at the same time transport the deionized water in the middle layer of the crystallization tube 7 back to the beaker 8. The deionized water circulation realizes natural cooling, and the ammonium sulfate solution slowly cools down until the first crystal is precipitated in the crystallization tube 7. Quickly record the temperature T at this time. nuc , complete the super solubility curve measurement under this fluorine content, the specific data are shown in the following table, and the metastable zone width ΔT of ammonium sulfate under this fluorine content is calculated max .
[0123] Table 2 Super solubility curve measurement data of Example 1
[0124] Serial number <![CDATA[Temperature T nuc (°C)]]> Mass m(g) Super Solubility S 1 70.4 100 1.00 2 59.6 95 0.95 3 44.8 90 0.90 4 31.5 85 0.85 5 18.2 80 0.80
[0125] Example 2
[0126] The method for determining the solubility of ammonium sulfate solution and the width of the metastable zone in the laboratory test section of this embodiment is specifically implemented as follows:
[0127] The steps for determining the solubility of ammonium sulfate solution are the same as those in Example 1, except that after weighing 100 g of ammonium sulfate, the fluorine element is introduced by ammonium fluoride, and the amount of ammonium fluoride required to be added is 0.20 g based on the mass percentage of fluoride ions in the ammonium sulfate sample being 0.1%.
[0128] Record the total mass m of ammonium sulfate sample added at each temperature T 总 , calculate the solubility S of the ammonium sulfate sample at each temperature T. The specific data are shown in the following table, and the solubility curve determination under this fluorine content is completed.
[0129] Table 3 Solubility curve measurement data of Example 2
[0130]
[0131]
[0132] The steps for determining the metastable zone width of ammonium sulfate solution are the same as those in Example 1, except that the fluorine content in the ammonium sulfate sample is 0.1%. The specific data are shown in the following table, and the metastable zone width ΔT of ammonium sulfate at this fluorine content is calculated. max .
[0133] Table 4 Super solubility curve measurement data of Example 2
[0134] Serial number <![CDATA[Temperature T nuc (°C)]]> Mass m(g) Super Solubility S 1 78.8 100 1.00 2 70.8 95 0.95 3 61.7 90 0.90 4 45.1 85 0.85 5 31.2 80 0.80
[0135] Example 3
[0136] The method for determining the solubility of ammonium sulfate solution and the width of the metastable zone in the laboratory test section of this embodiment is specifically implemented as follows:
[0137] The steps for determining the solubility of ammonium sulfate solution are the same as those in Example 1, except that after weighing 100 g of ammonium sulfate, the fluorine element is introduced by ammonium fluoride, and the amount of ammonium fluoride required to be added is 39.0 g based on the mass percentage of fluoride ions in the ammonium sulfate sample being 20%.
[0138] Record the total mass m of ammonium sulfate sample added at each temperature T 总 , calculate the solubility S of the ammonium sulfate sample at each temperature T. The specific data are shown in the following table, and the solubility curve determination under this fluorine content is completed.
[0139] Table 5 Solubility curve measurement data of Example 3
[0140] Serial number Temperature T(℃) <![CDATA[Total mass m 总 (g)]]> Solubility S (g / 100g water) 1 30 81.4 0.814 2 40 82.5 0.825 3 50 85.8 0.858 4 60 88.4 0.884 5 70 92.4 0.924 6 80 98.3 0.983 7 90 1.128 1.128
[0141] The steps for determining the metastable zone width of ammonium sulfate solution are the same as those in Example 1, except that the fluorine content in the ammonium sulfate sample is 20%. The specific data are shown in the following table: The metastable zone width ΔT of ammonium sulfate at this fluorine content is calculated. max .
[0142] Table 6 Super solubility curve measurement data of Example 3
[0143] Serial number <![CDATA[Temperature T nuc (°C)]]> Mass m(g) Super Solubility S 1 76.2 100 1.00 2 66.9 95 0.95 3 54.2 90 0.90 4 40.9 85 0.85 5 26.5 80 0.80
[0144] The solubility curves and super solubility curves of the above three examples are plotted to obtain the metastable zone of the corresponding ammonium sulfate solution, such as Figure 7 As shown. Figure 7 It can be seen that the metastable zone of the ammonium sulfate solution in Example 1 is the largest in width compared with the pure ammonium sulfate solution or other Examples 2-3, and the super solubility curve is located at the top, so that the ammonium sulfate solution with higher concentration after obtaining higher energy can also fall into the metastable zone.
[0145] Comparative Example 1
[0146] The specific implementation steps of the method for determining the solubility of ammonium sulfate solution and the width of the metastable zone in the laboratory test part of this comparative example are as follows:
[0147] The steps for determining the solubility of ammonium sulfate solution are the same as those in Example 1, except that after weighing 100 g of ammonium sulfate, no fluorine element is introduced. The total mass m of the added ammonium sulfate sample at each temperature T is recorded. 总 , calculate the solubility S of the ammonium sulfate sample at each temperature T. The specific data are shown in the following table, and the solubility curve determination is completed.
[0148] Table 7 Solubility curve determination data of Comparative Example 1
[0149] Serial number Temperature T(℃) <![CDATA[Total mass m 总 (g)]]> Solubility S (g / 100g water) 1 30 76.9 0.769 2 40 78.1 0.781 3 50 81.2 0.812 4 60 84.3 0.843 5 70 87.4 0.874 6 80 94.1 0.941 7 90 103.8 1.038
[0150] The steps for determining the width of the metastable zone of the ammonium sulfate solution are the same as those in Example 1, except that the fluorine element is not introduced in this comparative example. The specific data are shown in the following table: The width of the metastable zone of the ammonium sulfate solution ΔT is calculated. max .
[0151] Table 8 Super solubility curve measurement data of comparative example 1
[0152] Serial number <![CDATA[Temperature T nuc (°C)]]> Mass m(g) Super Solubility S 1 82.1 100 1.00 2 77.4 95 0.95 3 65.6 90 0.90 4 52.0 85 0.85 5 36.8 80 0.80
[0153] Comparative Example 2
[0154] The specific implementation steps of the method for determining the solubility of ammonium sulfate solution and the width of the metastable zone in the laboratory test part of this comparative example are as follows:
[0155] The steps for determining the solubility of ammonium sulfate solution are the same as those in Example 1, except that after weighing 100 g of ammonium sulfate, the fluorine element is introduced by ammonium fluoride, and the amount of ammonium fluoride required to be added is 58.48 g based on the mass percentage of fluoride ions in the ammonium sulfate sample being 30%.
[0156] Record the total mass m of ammonium sulfate sample added at each temperature T 总, calculate the solubility S of the ammonium sulfate sample at each temperature T. The specific data are shown in the following table, and the solubility curve determination under this fluorine content is completed.
[0157] Table 9 Solubility curve determination data of comparative example 2
[0158]
[0159]
[0160] The steps for determining the metastable zone width of ammonium sulfate solution are the same as those in Example 1, except that the fluorine content in the ammonium sulfate sample is 30%. The specific data are shown in the following table: The metastable zone width ΔT of ammonium sulfate at this fluorine content is calculated. max .
[0161] Table 10 Comparative Example 2 Super Solubility Curve Determination Data
[0162] Serial number <![CDATA[Temperature T nuc (°C)]]> Mass m(g) Super Solubility S 1 76.5 100 1.00 2 63.8 95 0.95 3 47.6 90 0.90 4 34.2 85 0.85 5 21.7 80 0.80
[0163] Comparative Example 3
[0164] The specific implementation steps of the method for determining the solubility of ammonium sulfate solution and the width of the metastable zone in the laboratory test part of this comparative example are as follows:
[0165] The steps for determining the solubility of ammonium sulfate solution are the same as those in Example 1, except that: after weighing 100 g of ammonium sulfate, the chlorine element is introduced by ammonium chloride, and the amount of ammonium chloride required to be added is 7.94 g according to the mass percentage of chloride ions in the ammonium sulfate sample being 5% (the amount of ammonium chloride added is calculated according to the method for calculating the amount of ammonium fluoride added).
[0166] Record the total mass m of ammonium sulfate sample added at each temperature T 总 , calculate the solubility S of the ammonium sulfate sample at each temperature T. The specific data are shown in the following table, and the solubility curve determination under this chlorine content is completed.
[0167] Table 11 Solubility curve measurement data of comparative example 3
[0168] Serial number Temperature T(℃) <![CDATA[Total mass m 总 (g)]]> Solubility S (g / 100g water) 1 30 77.1 0.771 2 40 78.6 0.786 3 50 81.8 0.818 4 60 85.2 0.852 5 70 87.9 0.879 6 80 94.7 0.947 7 90 104.6 1.046
[0169] The steps for determining the metastable zone width of ammonium sulfate solution are the same as those in Example 1, except that: in this comparative example, fluorine element is not introduced, and the chlorine content in the ammonium sulfate sample is 5%. The specific data are shown in the following table, and the metastable zone width ΔT of ammonium sulfate at this chlorine content is calculated. max .
[0170] Table 12 Super solubility curve measurement data of comparative example 3
[0171] Serial number <![CDATA[Temperature T nuc (°C)]]> Mass m(g) Super Solubility S 1 80.5 100 1.00 2 77.1 95 0.95 3 64.7 90 0.90 4 51.1 85 0.85 5 35.9 80 0.80
[0172] The solubility curves and super solubility curves of the above three comparative examples are plotted to obtain the metastable zone of the corresponding ammonium sulfate solution, such as Figure 8 As shown. Figure 8 It can be seen that the metastable zone widths of the ammonium sulfate solutions in Comparative Example 1 and Comparative Example 3 are substantially the same, and the metastable zone width of the ammonium sulfate solution in Comparative Example 2 is slightly wider than that in Example 1 and Example 3.
[0173] The metastable zone of the ammonium sulfate solution of Example 1 is compared with the metastable zone of the ammonium sulfate solution of Comparative Example 2. Fig. 9 As shown. Fig. 9 It can be seen that the metastable zone width of the ammonium sulfate solution in Example 1 is much larger than that in Comparative Example 2, and the super solubility curve is above that in Comparative Example 2.
[0174] like Fig.10 The following is an electron microscope image of ammonium sulfate grains with poor crystallization quality under high temperature conditions in summer. Fig.10 It can be seen that the grains are irregular in shape and small in size.
[0175] like Fig.11 The following is an electron microscope image of ammonium sulfate grains after adding fluorine. Fig.11 It can be seen that after adding fluorine, the ammonium sulfate crystals have regular crystal shape, clear edges and larger particle size.
[0176] From Table 1-6 and Figure 7-11 It can be seen that the addition of an appropriate amount of fluorine not only effectively increases the width of the metastable zone of the ammonium sulfate solution, but also shifts the super solubility curve of the ammonium sulfate solution upward, broadens the upper limit of the metastable zone of the solution, and allows the ammonium sulfate solution with more energy and higher concentration to fall within the metastable zone, thereby avoiding the explosive nucleation phenomenon of the ammonium sulfate solution due to the excessively high smoke temperature in summer, which causes the concentration to exceed the super solubility curve and fall into the unstable zone. Finally, an ammonium sulfate crystal product with controllable grain morphology and size is obtained, which ensures the stable operation of the device. The addition of chlorine in the comparative example cannot play the same role.
[0177] The present invention discloses a method for improving the crystal quality of ammonium sulfate solution. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the method. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The product of the present invention has been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the product described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
Claims
1. A method for improving the crystallization quality of ammonium sulfate solution, characterized in that: The following steps are involved: Step S1: determination of solubility of ammonium sulfate solution; A solubility determination test device is set up, deionized water is heated to an expected temperature T and kept constant; fluoride is weighed and added to ammonium sulfate, and ammonium sulfate samples with different fluorine contents are obtained after being fully mixed; the ammonium sulfate sample is weighed and added to the deionized water heated to the expected temperature T, and a constant rate of magnetic stirring is started, and the ammonium sulfate sample is added in small amounts multiple times until a very small amount of the ammonium sulfate sample cannot be dissolved within the specified time, and the total mass of the added ammonium sulfate sample is recorded, the solubility of the ammonium sulfate sample at the temperature T is calculated, and the corresponding solubility curve is drawn; Step S2: Determination of the width of the metastable zone of the ammonium sulfate solution; Weigh a certain amount of fluoride and add it to a certain amount of ammonium sulfate, mix them thoroughly and evenly to obtain ammonium sulfate samples with different fluorine contents; use a solubility test device to mix deionized water and the ammonium sulfate sample, and then use a water bath and a peristaltic pump to circulate and heat them, while starting a magnetic stirring at a constant rate until the ammonium sulfate sample is completely dissolved; build a metastable zone test device, quickly pour the obtained ammonium sulfate solution into a crystallization tube (7) in the metastable zone test device, and achieve natural cooling through the circulation of deionized water. The ammonium sulfate solution slowly cools down until the first crystal is precipitated in the crystallization tube (7), and the temperature T at this time is recorded. nuc ; Determine the temperature T of each ammonium sulfate sample with the same fluorine content and different concentrations nuc , draw the super solubility curve of each sample and calculate the width of its metastable zone respectively; Step S3: Determine the optimal amount of fluorine added based on the solubility of the ammonium sulfate sample calculated in step S1 and the metastable zone width of the ammonium sulfate solution calculated in step S2, and introduce fluorine into the flue gas ammonia desulfurization system so that the ammonium sulfate solution in the system can be within the metastable zone when the concentration is high.
2. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that, The solubility determination test device comprises: Jacketed crystallizer (1); A magnetic stirrer (3) installed at the lower end of the jacketed crystallizer (1); A magnetic stirrer (4) is placed at the bottom of the jacketed crystallizer (1); a water bath (6) connected to the jacketed crystallizer (1) via a first peristaltic pump (5); Two first digital thermometers (2), one of the first digital thermometers (2) is mounted on the jacketed crystallizer (1) and a measuring end of the first digital thermometer (2) is inserted into the jacketed crystallizer (1), and the other first digital thermometer (2) is mounted on the water bath (6) and a measuring end of the first digital thermometer (2) is inserted into the water bath (6); Accurately measure a certain amount of deionized water and pour it into a water bath (6). Use the water bath (6) to heat the deionized water to a desired temperature T and keep it constant. Then use a first peristaltic pump (5) to transport the deionized water heated to the desired temperature T to the jacketed crystallizer (1). At the same time, transport the deionized water in the jacketed crystallizer (1) back to the water bath (6) for circulation heating to keep the temperature of the deionized water constant at the desired temperature T. During the heating process, the deionized water temperature is checked in real time by a first digital thermometer (2).
3. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that: The metastable zone determination test device comprises: Iron frame (9); A crystallization tube (7) fixed on an iron frame (9), wherein the crystallization tube (7) is a three-layer crystallization tube structure, wherein the innermost layer is used for standing and crystallizing the ammonium sulfate sample solution, the middle layer is used for running water to maintain the temperature of the ammonium sulfate sample solution, and the outermost layer is an air layer for further heat preservation; A beaker (8) connected to the middle layer of the crystallization tube (7) via a second peristaltic pump (11), the lower end of the crystallization tube (7) is inserted into the beaker (8), and the water level in the beaker (8) is above the lower water inlet of the crystallization tube (7); A second digital thermometer (10) is mounted on the crystallization tube (7) and has a measuring end inserted into the crystallization tube (7).
4. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that: In step S1, the expected temperature is 30°C to 90°C.
5. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that: In step S1, in the ammonium sulfate samples with different fluorine contents, the fluoride ion accounts for 0.1% to 20%.
6. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that: In step S1, the fluoride is selected from one of ammonium fluoride, sodium fluoride, calcium fluoride and aluminum fluoride.
7. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that: In step S1, the fluoride is ammonium fluoride, and the calculation method of the addition amount of ammonium fluoride m(NH4F) in the ammonium sulfate sample is as follows: because Therefore, the mass of ammonium fluoride added in, is the mass percentage (%) of fluorine element in the ammonium sulfate sample, n is the amount of fluorine element and ammonium fluoride substance added, m(water) is the mass of deionized water, M(F) is the relative atomic mass of fluorine, and M(NH4F) is the molecular weight of ammonium fluoride.
8. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that: In step S1, the calculation formula of the solubility S of the ammonium sulfate sample is as follows: Among them, m 总 is the total mass of the ammonium sulfate sample, m 水 is the mass of the solvent, i.e., deionized water.
9. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that: The constant speed range is 150r / min to 1500r / min.
10. A method for improving the crystallization quality of ammonium sulfate solution according to claim 1, characterized in that: In step S2, the calculation method of the metastable zone width is as follows: The width of the metastable zone refers to the distance between the supersolubility curve and the solubility curve of the system. The vertical distance represents the maximum supersaturation Δc. max : Δc max =c0-c2 Where c0 is the saturated concentration of ammonium sulfate solution at a certain temperature, and c2 is the concentration at which crystal nuclei appear at that temperature; Its horizontal distance represents the maximum undercooling ΔT max , which is the difference between the saturation temperature and the nucleation temperature: ΔT max =T0-T nuc Among them, T0 is the saturation temperature of the solution at a certain concentration, T nuc is the temperature at which the crystal nucleus appears at this concentration; Maximum supersaturation Δc max and maximum subcooling ΔT max The relationship between them is: Where dC* / dT is the slope of the solubility curve.
Citation Information
Patent Citations
Purification technology for side product of flue gas ammonia-desulphurization
CN102826572A
Device and method for enhancing quality of ammonia-process desulfurization coproduct ammonium sulfate
CN106345257A
Method for regulating ammonium sulfate metastable zone by mixing ammonium chloride and ammonium nitrate and application
CN115417430A